Analgetic effectiveness of fenugreek seed extract (Trigonella foenum-graecum L.) in acetic acid-induced male ddY strain mice - Riska Okta Via; Dewi Damayanti Abdul Karim; Andreanus Andaja Soemardji; Refsya Azanti Putri (Fakultas Sains Institut Teknologi Sumatera, 2025)
Pain represents a significant health challenge, with current nonsteroidal anti-inflammatory drugs (NSAIDs) carrying hepatotoxicity risks that necessitate safer alternatives. This study evaluated the analgesic activity of fenugreek (Trigonella foenum-graecum L.) seed extract using the acetic acid-induced writhing test in male ddY strain mice. Twenty-five mice were randomly allocated into five groups (n=5): negative control (1% Na-CMC), positive control (diclofenac sodium 50 mg/kg), and three fenugreek extract groups (200, 400, and 600 mg/kg). Pain was induced by intraperitoneal injection of 1% acetic acid, and writhing episodes were counted for 180 minutes. Data were analyzed using one-way ANOVA with Tukey's post-hoc test. All fenugreek doses significantly reduced writhing compared to negative control (p < 0.05). The extract demonstrated dose-dependent analgesic activity, with protection rates of 30.8%, 35.9%, and 41.0% for 200, 400, and 600 mg/kg doses, respectively. The highest dose (600 mg/kg) achieved 71% of diclofenac's analgesic efficacy (46.2% protection). Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, steroids, tannins, and polyphenols. These findings suggest fenugreek seed extract possesses significant analgesic properties and represents a promising natural alternative for pain management.